Fractures of the transverse processes of the fourth and fifth lumbar vertebrae in patients with pelvic ring injuries: indicator of biomechanical instability but not shock. (September 2018) - Winkelmann, M.; Lopez Izquierdo, M.; Clausen, J-D.; Liodakis, E.; Mommsen, P.; Blossey, R.; Krettek, C.; Zeckey, C.
Abstract : Aims: This study aimed to analyze the correlation between transverse process (TP) fractures of the fourth (L4) and fifth (L5) lumbar vertebrae and biomechanical and haemodynamic stability in patients with a pelvic ring injury, since previous data are inconsistent. Patients and Methods: The study is a retrospective matched-pair analysis of patients with a pelvic fracture according to the modified Tile AO Müller and the Young and Burgess classification who presented to a level 1 trauma centre between January 2005 and December 2014. Results: A total of 728 patients with pelvic ring injuries were included, of whom 183 (25.1%) had a biomechanically unstable pelvic fracture. Of these patients, 84 (45.9%) had a fracture of a TP of L4 and/or L5. A total of 73 patients (13.4%) with a stable pelvic ring injury (p < 0.001) had a fracture of a TP. Patients with a fracture of a TP of L4 and/or L5 had a 5.5-fold risk (odds ratio (OR)) of having a biomechanically unstable pelvic injury. TP fractures (OR 1.6, p = 0.2) could not be confirmed as an independent predictor of haemodynamic instability. Conclusion: This is the first study that has demonstrated a positive correlation between a TP fracture of L4 and/or L5 and a biomechanically unstable pelvic ring injury. The presence of transverse process fractures of L4 and/or L5 indicates increased severity of pelvic injury and therefore can help in the planning of emergency treatment. Cite this article: Bone Joint J 2018;100-B:1214–19.